The Impact of Jigsaw Method on Students’ Interactive Communication Abilities - Lutfiah Nur Athifah; Sultan Baa; Fitri Radhiyani (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
The impact of the Jigsaw cooperative learning approach in enhancing the interactive communication skills of seventh-grade students at SMP Muhammadiyah 14 Makassar is examined in this article. Fluency, pronunciation, grammar, vocabulary, and content are the five communication indicators where students' performance is analyzed in this quantitative study using a pre-experimental design with pre-test and post-test evaluations. After using the Jigsaw technique, students' interactive communication skills significantly improved, according to the results, which were analyzed using descriptive statistics and the Wilcoxon Signed-Ranks Test. According to these results, students' verbal engagement and communicative ability in English language classes are significantly enhanced by structured peer cooperation.